Hubungan antara Motivasi Belajar dengan Self Directed Learning Readiness pada Mahasiswa Tahun Pertama Fakultas Kedokteran Universitas Sam Ratulangi - Ngongoloy, Johanes J. F.; Berhimpon, Siemona; Pangemanan, Damajanty (Universitas Sam Ratulangi, 2024)
Abstract: Learning methods of Student Centered Learning indirectly demand students to study independently. Self-directed learning readiness (SDLR) or the readiness of students to the independence learning is something that medical students must have. Self-directed learning readiness is influenced by several factors, one of them is motivation to learn. This study aimed to determine the relationship between learning motivation and SDLR of first year students at the Faculty of Medicine, Universitas Sam Ratulangi. This was an observational and analytical study using a cross-sectional design. There were two types of questionnaires which were the motivated strategies for learning questionnaire (MSLQ) to assess learning motivation and the self-directed learning readiness scale (SDLRS) to assess readiness for independent learning. The Spearman test showed that there was a significant relationship between learning motivation and SDLR (p-value=0.000), with a strong and positive correlation (r=0.557) among the first-year students of Faculty of Medicine Universitas Sam Ratulangi. In conclusion, there is a significant relationship between learning motivation and self-directed learning readiness (SDLR) with a strong and positive correlation. Keywords: medical students; learning motivation; learning methods Abstrak: Metode pembelajaran Student Centered Learning secara tidak langsung menuntut mahasiswa untuk belajar secara mandiri. Self-directed learning readiness (SDLR) atau kesiapan belajar mandiri merupakan hal yang harus dimiliki mahasiswa fakultas kedokteran. Tingkat SDLR dipengaruhi oleh beberapa faktor, salah satunya ialah motivasi belajar. Penelitian ini bertujuan untuk mengetahui hubungan antara motivasi belajar dengan SDLR mahasiswa tahun pertama Fakultas Kedokteran Universitas Sam Ratulangi. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Terdapat dua jenis kuisioner yang digunakan yaitu Motivated Strategies for Learning Questionnaire (MSLQ) untuk menilai motivasi belajar dan Self Directed Learning Readiness Scale (SDLRS) untuk menilai kesiapan belajar mandiri. Hasil analisis data menggunakan uji korelasi Spearman menunjukkan bahwa terdapat hubungan bermakna antara motivasi belajar dan SDLR (p=0,000), kekuatan korelasi kuat (r=0,557), dan hubungannya berpola positif yang berarti semakin tinggi motivasi belajar maka akan semakin tinggi juga tingkat SDLR. Simpulan penelitian ini ialah terdapat hubungan bermakna antara motivasi belajar dan self-directed learning readiness (SDLR) dengan tingkat keeratan kuat dan memiliki arah positif. Kata kunci: mahasiswa kedokteran; motivasi belajar; metode pembelajaran